(untitled) (Revista LIDER, 2020)
The processes of economic integration represent a challenge for local markets. The demands associated with integration economical implies not only the transformation of productive activities and the replacement of traditional methods, also the employment is changed. How socio-economic development of the population is enhanced to build more competitive territories? To answer, this analysis favors the statistical approach, and the methodology provides sufficient empirical evidence to say that the progress of certain characteristics of the population contributes to raise its socio economic potential. Then, to decipher how these factors are involved in the transformation of a society, be possible devise strategies to promote territorial development.